Case Report: Sequential PTCD and biliary seed stent combined with targeted-immunotherapy for advanced pancreatic cancer with malignant obstructive jaundice: a multidisciplinary approach - Li, Weijun; Sun, Guoyang; Zhu, Rui; Li, Pindong; Wang, Li (Frontiers in Oncology, 2025)
Malignant obstructive jaundice (MOJ) due to tumor compression or invasion of the bile duct carries a grave prognosis. We report a case of a 54-year-old female patient (height: 160 cm, weight: 55 kg, BMI: 21.5 kg/m², ECOG performance status: 1, with type 2 diabetes mellitus) advanced pancreatic head cancer causing MOJ, managed with a multidisciplinary approach. Initial endoscopic retrograde cholangiopancreatography (ERCP) with an 8.5 Fr plastic stent failed due to occlusion after 20 days, leading to bilirubin rebound. Emergency percutaneous transhepatic cholangial drainage (PTCD) followed by biliary metal stent (8 mm × 80 mm) and iodine-125 seed implantation effectively relieved obstruction, reducing total bilirubin (TBIL) from 116.9 to 45.6 μmol/L within seven days. Subsequent tomotherapy (TOMO, 66 Gy to gross tumor volume) and a personalized regimen of S1 (tegafur, 20 mg/day), nimotuzumab, and pembrolizumab, following intolerance to gemcitabine + nab-paclitaxel (AG), achieved a 78% reduction in CA19–9 and sustained biliary patency. At one-year follow-up, TBIL was 18.2 μmol/L, direct bilirubin (DBIL) was 9.8 μmol/L, and the patient reported a good quality of life (Karnofsky score: 90). This case demonstrates the efficacy of sequential PTCD, seed stent, and targeted-immunotherapy, offering a practical model for managing advanced pancreatic cancer with MOJ.